Boj za glagoljaško liturgijo v luči poročanja avstrijskih namestnikov v Zadru med letoma 1902–1913 - Hajdinac, Sara (Retrospektive, 2024)
Due to its use of Old Slavic language and Glagolitic writing, Glagolist liturgy represented the only non-Romance enclave within the RomanCatholic religious tradition, having had been common mainly in Venetian Stato da Mar. After the collapse of the Venetian Republic, Glagolist tradition, despite government oppression, persisted as far as into the 20th century when the question of language in liturgy in Croatia began permeating into the political sphere. A rich source that brings to light the strife to preserve Glagolist liturgy is provided by Austrian deputies in Zadar, who submitted regular and precise reports to Imperial-Royal Ministry of Internal A airs in Vienna. This paper provides insight into the struggle for Glagolist liturgy through the reports of deputies Erasmus von Handel, Nikolaus Nardelli, and Count Marius of Attems-Heiligenkreuz.
Keywords: C.-kr. ministrstvo za notranje zadeve; Glagolitism; glagoljaštvo; Liturgija; Ministry of the interior; old Slavic liturgy; staroslovanska liturgija; Statthalter in Zara; Zgodovina